2015
DOI: 10.4081/ejtm.2015.4910
|View full text |Cite
|
Sign up to set email alerts
|

Functional electrical stimulation as a safe and effective treatment for equine epaxial muscle spasms: Clinical evaluations and histochemical morphometry of mitochondria in muscle biopsies

Abstract: Functional Electrical Stimulation (FES) has been used extensively over several decades to reverse muscle atrophy during rehabilitation for spinal cord injury patients. The benefits of the technology are being expanded into other areas, and FES has been recently utilized for injury rehabilitation and performance enhancement in horses. Six retired horses (age from 10 to 17 yrs) that had been previously used mainly for dressage riding were selected for this study. Clinical evaluation found epaxial muscle spasms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…7 B ). 23 It is interesting to note that, in recent observations comparing young and very old (30 months) rat muscles (EDL, soleus and diaphragm) subjected to neurectomy, 24 we found that the abundance of subsarcolemmal mitochondria decreases with age and even more so after one week of denervation, whatever the animal age (manuscript in preparation). Feliciano Protasi and others have shown very interesting data concerning the structural relationships of mitochondria with triads in the intermyofibrillar spaces.…”
Section: A Horse Model To Assess Fes Effectiveness By Morphometry Of mentioning
confidence: 61%
See 1 more Smart Citation
“…7 B ). 23 It is interesting to note that, in recent observations comparing young and very old (30 months) rat muscles (EDL, soleus and diaphragm) subjected to neurectomy, 24 we found that the abundance of subsarcolemmal mitochondria decreases with age and even more so after one week of denervation, whatever the animal age (manuscript in preparation). Feliciano Protasi and others have shown very interesting data concerning the structural relationships of mitochondria with triads in the intermyofibrillar spaces.…”
Section: A Horse Model To Assess Fes Effectiveness By Morphometry Of mentioning
confidence: 61%
“…Indeed, only one horse presents with obvious evidence of post-FES muscle damage (foci of severe muscle fiber atrophy) whereas the other 5 horses, which had the same type and amount of electrical stimulation, display only scanty evidence of muscle atrophy (possibly resulting from denervation) in both pre- and post-stimulation biopsies. 23 …”
Section: A Horse Model To Assess Fes Effectiveness By Morphometry Of mentioning
confidence: 99%
“…Em consonância a terapia, foi realizada a estimulação elétrica funcional (FES) para fortalecimento muscular do equino. Essa modalidade de fisioterapia tem sido usada como um meio para reduzir ou reverter a atrofia muscular, além de obter uma recuperação funcional em equinos com lesão medular (RAVARA et al, 2015). Seu uso foi eficaz, e, após 30 dias de treinamentos alternados com duração de 20 minutos, o animal apresentou melhora na atrofia muscular (Figura 1B) e em seu desempenho atlético, conseguindo realizar as atividades a que foi destinado, principalmente o salto com obstáculos.…”
Section: Discussionunclassified
“…8 Work by Ugo Carraro found similar changes in skeletal muscle that had been in a state of chronic spasm. 9 Chronic spasm of skeletal muscle, in a similar way as found in cardiac muscle, induces a state of chronic ischemia. He showed reversibility of the light microscopy structural changes with therapy of the chronic spasm.…”
Section: Skeletal and Cardiac Muscle Similaritiesmentioning
confidence: 94%